AKUISISI GOOGLE DRIVE ANDROID MENGGUNAKAN OXYGEN DAN MOBILedit DENGAN METODE NATIONAL INSTITUTE OF JUSTICE - Jeki Kuswanto; Nur Asyifa; Ibnu Hadi Purwanto (Jurnal Informatika Teknologi dan Sains (Jinteks), 2023)
Smartphones are clear evidence of the development of digital technology. Currently, smartphones are also experiencing developments in storage media, one of which is cloud storage. This is a new challenge for forensic IT and or law enforcement in conducting investigations of various digital crimes on Google Drive cloud storage media on Android. The method used in conducting research to deal with forms of crime with smartphone media evidence is the National Institute Of Justice (NIJ) method. Researchers get more related information: Account addresses from users/users, passwords from users/users, files in the form of photos, videos, RAR, and document files can detect files that have been deleted. While using MOBILedit Forensic tools. In the MOBILedit Tools, researchers only get some information contained on smartphones in the form of Image files, Wifi networks, and GPS location. And from the results of the comparison of the success of the two tools, namely oxygen forensics, as much as 100%, while MOBIL forensic editing, as much as 20%.